The Gojek Way: An Instrumental Branded Content Analysis of #PastiAdaJalan Campaign - Amienah Atthahirah; Gerry Maulana; M Irsyad Jamin; Rexy Fajrin Ismail; Sekar Anugrah Resky; Wiyanie Putri (Graduate School of Communication Universitas Bakrie, 2025)
This article analyses the communication strategy of the Gojek brand, an online transportation service, through its campaign entitled #PastiAdaJalan. Using the instrumental Branded Content Analysis (BCA) method, this study finds various ways Gojek communicates its brand value as a solution for urban communities in meeting their urban needs and problems, such as anti-congestion transportation, online food ordering, online payments, and many more, yet another online service that accompanies consumer mobility. The slogan and hashtag #PastiAdaJalan is a crucial message that conveys Gojek's promise as a brand that provides integrated, practical and efficient technological service solutions. This study provides important insights for brands in communicating their brand simply, focused, and consistently through creative and meaningful content.